Esotropia in Douin Syndrome and Ways to Improve the Results of Surgical Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
This article presents an extensive study on the clinical features of esotropia in Duane retraction syndrome (DRS) and the optimization of surgical approaches aimed at improving ocular alignment, reducing abnormal head posture, and enhancing binocular function. Duane syndrome, a congenital ocular motility disorder characterized by co-contraction of the medial and lateral rectus muscles, often leads to esotropic deviation due to mechanical and innervational anomalies. The research analyzes various surgical techniques, including medial rectus recession, lateral rectus resection, and transposition procedures, assessing their efficacy, safety, and postoperative outcomes. The study also emphasizes the importance of individualized surgical planning based on the type of DRS, degree of esotropia, limitation of abduction, and presence of globe retraction or up/downshoots. Findings indicate that a tailored, minimally invasive surgical approach, combined with precise preoperative evaluation and long-term follow-up, significantly improves functional and cosmetic outcomes. The research provides an evidence-based framework for enhancing surgical correction in patients with Duane syndrome-associated esotropia. This article provides a comprehensive evaluation of esotropia associated with Duane retraction syndrome (DRS) and explores advanced surgical approaches aimed at improving alignment, reducing abnormal head posture, and restoring binocular function. Duane syndrome is a congenital ocular motility disorder resulting from aberrant innervation of the lateral rectus muscle by branches of the oculomotor nerve, leading to limited abduction, globe retraction, and esotropic deviation in the primary gaze position. The research emphasizes individualized surgical strategies such as graded medial rectus recession, lateral rectus transposition, and Y-splitting procedures to address the unique pathophysiology of the syndrome. Through detailed preoperative assessment and postoperative follow-up, the study demonstrates that tailored, minimally invasive interventions significantly enhance ocular alignment, improve motility, and achieve superior functional and aesthetic outcomes. The findings support a patient-specific, anatomically informed approach as essential for achieving stable and long-lasting results in the management of esotropic Duane syndrome.